A comparative study of electrodeposited and vapour deposited gold films : Fractal surface characterization through scanning tunnelling microscopy - Herrasti, P. (1992)
The surfaces of Au deposits grown under non-equilibrium conditions from either the electroreduction of Au oxide or from the vapour have been analysed as fractals by measuring the perimeter (P) and the area (A) of intergranular voids. The values of P and A were determined from scanning tunnelling microscopy (STM) topographic imaging of the deposit surfaces. A frsctal behaviour P ∝ 4 D/2 was found with D = 1.5 ± 0.1 and D = 1.7 ± 0.1 for the electrodeposited and vapour deposited Au iilms, respectively. These figures remain constant for film thicknesses between 100 and 1000 mn. The value of D, the fractal dimension of the surfaces, is 2.5 ± 0.1 for the Au electrodeposits, and 2.7 + 0.1 for the Au vapour deposited films. The former value is consistent with either a diffusion or an electric field controlled growth model, whereas the latter is in agreement with a ballistic growth model.